The Role of Teledentistry in the Early Detection of Oral Lesions: A Systematic Review of Diagnostic Accuracy - Miura A. Kuswara; Merita Arini (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Diagnosis of oral lesions, especially potentially malignant lesions, is complicated by their asymptomatic presentation and variable clinical appearance. Delayed diagnosis in rural areas where there are few specialists may lead to high morbidity and mortality rates. The use of teledentistry as an innovative tool to detect oral lesions has been explored. The present study aims to explore the application of teledentistry for the early diagnosis of oral lesions, examining diagnostic accuracy, advantages, clinical challenges, and future potential. Methods: Publications from the last 10 years were chosen based on specific inclusion criteria. The present systematic review was conducted in accordance with the PRISMA guidelines. Studies assessing diagnostic accuracy were critically appraised using the QUADAS-2 tool, while other types of studies were critically appraised using the appropriate JBI critical appraisal tool. In total, 11 studies were included. Results: The majority of the research used store-and-forward (SAF) methods, with some using real-time consultations. Studies have indicated that there is a high level of agreement with face-to-face consultation (kappa > 0.80). It was recognized that it avoids unnecessary referrals as well as improves access to healthcare services in areas with minimal medical facilities. The limitations involved are problems relating to imaging quality, the need for palpation, and proper training of the operators involved. Conclusion: Teledentistry serves as a useful alternative for diagnosing mouth lesions in their initial stages. Despite the fact that it does not substitute for face-to-face consultations, it can be an potential screening and triage tool.